Metabolit Sekunder dan Uji Bioaktivitas Sitotoksik Ekstrak Buah Sumpit (Brucea javanica (L.) Merr) terhadap Artemia salina Leach - Nur, Tajuddin; Rusman, Arman; Hikmawan, Baso Didik; Almaida, Maria; Herman; Ibrahim, Arsyik (B-Creta Publisher, 2024)
Research carried out with the title of Secondary Metabolite Identification and bioactivity Fruit Extract Sumpit (Brucea javanica (L) Merr) to the shrimp larvae Artemia salina Leach. This study aims to identifying classes of secondary metabolites as well as test the bioactivity of secondary metabolites sumpit. Identifikasi fruit extracts performed to test the Chopsticks fruit extracts and fractions against reagent, while the bioactivity test was conducted using Brine Shrimp Lethality Test (BSLT). Data were analyzed using the method of Reed and Muench to get Lethality Concrentation value 50% (LC50). The results showed that the fruit extract Sumpit contain the alkaloid class of secondary metabolites, karatenoid, saponins, tannins, phenolic compounds, steroids, and terpenoids. Sumpit fruit bioactivity test results had LC50 values of the methanol extract of 3.10 ppm, n-hexane fraction of 2.09 ppm, 0.79 ppm ethyl acetate fraction and n-butanol fractions of 0.74 ppm.